Avascular necrosis in patients with chronic myeloid leukemia: A systematic review: CML and AVN - Yassin, Mohamed; Al-Mashdali, Abdulrahman F; Al-Dubai, Husam N (Acta Biomedica Atenei Parmensis, 2022)
Abstract.  Objective: Avascular necrosis (AVN)has been encountered in hematological malignancies; nonetheless, AVN is extremely uncommon in patients with chronic myeloid leukemia (CML). This review aims to describe the pathophysiology, clinical characteristics, and outcomes of AVN in CML. To our knowledge, this is the first systematic review of this topic. Methods: We searched PubMed and Google Scholar for the case reports and series of patients with CML who developed AVN from inception to July 2021. Results: We found 21 cases of AVN in CML patients,17 cases with avascular necrosis of the femoral head (AVNFH), and four cases with osteonecrosis of the jaw (ONJ). The median age was 39 years with an almost equal distribution between males and females (ratio of 1:1). AVN related to CML management has been linked to tyrosine kinase inhibitors (TKIs) and standard interferon-alpha (IFN-α) therapies. Only six (out of 17) patients who developed AVN of the femoral head eventually required a hip replacement, and one (out of 17) developed a recurrent episode of AVNFH. All the reported cases of CML with osteonecrosis of the jaw were associated with TKIs therapy. Conclusion: Clinician should consider AVN in any CML patient complaining of either hip or jaw pain. IFN-α and TKI therapies can predispose to AVN in CML patients. Further studies are required for a better understanding of this condition in CML.